Innovation in facilities maintenance management - Pitt, M.; Goyal, S.; Sapri, M. (Chartered Institution of Building Services Engineers, 2006)
This paper highlights the function and the implications of a strategic maintenance management system in relation to building maintenance performance. The paper examines the technical and management functions in building maintenance and highlights the issues of quality management, contract management, resourcing strategy and the innovation processes required in the organizational drive towards effective and efficient maintenance management systems. The paper concludes that innovative solutions to maintenance issues are essential for continued efficiency and are brought about through the creation of an environment in which creativity is able to thrive.